AN ANALYSIS OF SPEECH ACT TYPES OF EXPRESSIVE IN DGS BY BROWN BAG FILMS - Fristi Arfiawati; Rossantiana Agus (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The research which titled An Analysis of Speech Act Types in DGS by Brown Bag Films purposed to analyze the types of speech act based on Searle’s theory. The research applied descriptive qualitative method and  used digital storytelling videos by Brown Bag Films as the data. The data were taken from utterances spoken in digital storytelling videos, and analyzed by using the theory of speech acts types. The research focus on an expressive utterances in DGS video. Expressive can be in the forms of greetings, apologizing, condoling, praising, excusing, mocking, worrying, congratulating, thanking and many kind of expressions. The result showed that there were six types of expressive utterances in digital storytelling videos that comprise into praising acts, greeting acts, excusing acts, apologizing act, mocking acts, and expressing acts.utterances in the Digital Storytelling video by Brown Bag Film.